Blood pressure among Australian Aboriginal children. Issue 9 (September 2017) - Larkins, Nicholas; Teixeira-Pinto, Armando; Banks, Emily; Gunasekera, Hasantha; Cass, Alan; Kearnes, Jane; Craig, Jonathan C.
Abstract : Objectives: To determine the prevalence of elevated blood pressure (BP) and potential predictors of SBP and DBP in urban Australian aboriginal children. Methods: The Study of Environment on Aboriginal Resilience and Child Health is a prospective cohort study of urban Aboriginal children attending four Aboriginal Community Controlled Health Services in New South Wales, Australia. Clinical measures included a manual BP measured by research officers using standardized protocols. BP z -scores adjusted for sex, age, and height were used in regression analyses. Hypertension was defined as a BP at least 95th centile and prehypertension at least 90th centile. Factors considered in relation to BP included child (BMI, dietary history, socioeconomic status, sedentary behavior) and caregiver measures (BP and caregiver stress). Results: Overall, data from 657 children, aged 2–17 years and their caregivers, collected from 2008 to 2011, were included. Median child age was 6.3 years (interquartile range: 4.0, 9.9); 15.6% (95% confidence interval 12.2–19.1%) had hypertension and 12.3% (9.2–5.5%) prehypertension. Following adjustment, the strongest predictor of BP was caregiver BP (0.15 increase in systolic z -score per 10 mmHg of caregiver BP, 95% confidence interval 0.07–0.24, P < 0.001); child BMI z -score was significantly related to diastolic [0.08 increase (0.01–0.15) per mg/m 2 BMI increase, P = 0.03] but not SBP [0.08 increase (−0.01 to 0.16) per mg/m 2 BMI increase, P = 0.08]. None of the other factors examined were significantly related to BP. Conclusion: BP is frequently elevated in urban aboriginal children. The strongest predictors of BP were caregiver BP and child BMI. Based on these data, and given the strong community linkages of aboriginal people, we recommend family-based interventions to reduce BP in this high-risk group. Abstract : Supplemental Digital Content is available in the text